(untitled) (Global Journal of Human-Social Science, 2024)
The Bulldog Transit System BTS is managed by the AAMU Transport Department Its objective is to make students mobility on campus easier by busing them around the university s beautiful campus AAMU Transport Department Website AAMU students have transport mode option of using the campus BTS to facilitate their mobility on campus The purpose of this study is to explore students perception about the operations of the campus BTS Descriptive statistics such as simple frequency distribution percentages mean and mode variance cross tabulation graphs and charts was used in the study Also correlation and regression analysis was used to establish relationships between variables The target population of this study involved the entire undergraduate and graduate students of the Alabama A M University Statistical Package for Social Sciences SPSS and excel was used for the data analysis The research found that students who stay on campus majority of whom are freshmen prefer to walk than to use the bus system to campus